2023
DOI: 10.1111/jon.13109
|View full text |Cite
|
Sign up to set email alerts
|

Imaging biomarkers of cerebral edema automatically extracted from routine CT scans of large vessel occlusion strokes

Abstract: Background and Purpose Volumetric and densitometric biomarkers have been proposed to better quantify cerebral edema after stroke, but their relative performance has not been rigorously evaluated. Methods Patients with large vessel occlusion stroke from three institutions were analyzed. An automated pipeline extracted brain, cerebrospinal fluid (CSF), and infarct volumes from serial CTs. Several biomarkers were measured: change in global CSF volume from baseline (ΔCSF); ratio of CSF volumes between hemispheres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…50 NWU can be inferred from changes in the attenuation coefficient or directly visualized on MRI DWI sequences and reflects the extent of water uptake in the brain. 51 In a post hoc analysis of 81 patients from the GAMES-RP Trial, it was shown that NWU on the admission CT scans was higher in patients who later developed malignant edema compared with those who did not and was an independent predictor for malignant edema after adjusting for baseline midline shift. 52 To determine whether different radiographic biomarkers predict edema endpoints, one study compared several radiographic biomarkers including change in global CSF volume, the ratio of CSF volumes between hemispheres, and NWU.…”
Section: Potential Quantitative Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…50 NWU can be inferred from changes in the attenuation coefficient or directly visualized on MRI DWI sequences and reflects the extent of water uptake in the brain. 51 In a post hoc analysis of 81 patients from the GAMES-RP Trial, it was shown that NWU on the admission CT scans was higher in patients who later developed malignant edema compared with those who did not and was an independent predictor for malignant edema after adjusting for baseline midline shift. 52 To determine whether different radiographic biomarkers predict edema endpoints, one study compared several radiographic biomarkers including change in global CSF volume, the ratio of CSF volumes between hemispheres, and NWU.…”
Section: Potential Quantitative Biomarkersmentioning
confidence: 99%
“…The authors concluded that CSF volumetric biomarkers could be automatically measured from almost all routine CTs and correlated better with standard edema endpoints than NWU. 51 While CSF and NWU are not yet standardly available or used in clinical practice, improved imaging processing and segmentation technology may make these measurements more widely available in the future.…”
Section: Potential Quantitative Biomarkersmentioning
confidence: 99%